Nosocomial oral myiasis in an intensive care unit - Gutierrez, Alejandro (2019)
We present the case of nosocomial myiasis, which occurred in a Peruvian hospital, whose etiological agent was identified as Cochliomyia hominivorax, associated with an 82-year-old patient who was admitted to an intensive care unit, due to acute respiratory failure type I, and sepsis due to abscess hepatic, which underwent intubation to provide assisted mechanical ventilation. On the third day of admission to the ICU, multiple mature larvae were observed in the oral cavity. The treatment consisted of the manual extraction of the larvae, and ivermectin therapy at a rate of 0,2 milligrams per kilogram of weight with favorable response. One month after being diagnosed with myiasis. The patient died of complications of hepatic sepsis and pneumonia.